2012
DOI: 10.1093/infdis/jis573
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology of Influenza-Like Illnesses in Cameroon, January–December 2009

Abstract: We found that respiratory viruses play an important role in the etiology of ILI in Cameroon, particularly in children <5 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
81
5
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 32 publications
31
81
5
1
Order By: Relevance
“…A study conducted in Kenya reported 16.5% of severe pneumonia cases were RSV-associated, consistent with our findings [18]. The percentage of RSV positivity in Iran, however, was higher than in countries such as Cameroon (5.7%) [19] and Kenya (12.5%) [20], but lower than in recent reports from Latvia (33% to 57%) [21] and Turkey (37.9%) [22]. The rate of RSV detection varied over time in studies conducted in Iran, with low and high rates of 5.7% and 45.8% reported in 2007 and between 2009 and 2011, respectively (Table 1).…”
Section: Results Prevalence Of Rsv Circulating In Iransupporting
confidence: 90%
“…A study conducted in Kenya reported 16.5% of severe pneumonia cases were RSV-associated, consistent with our findings [18]. The percentage of RSV positivity in Iran, however, was higher than in countries such as Cameroon (5.7%) [19] and Kenya (12.5%) [20], but lower than in recent reports from Latvia (33% to 57%) [21] and Turkey (37.9%) [22]. The rate of RSV detection varied over time in studies conducted in Iran, with low and high rates of 5.7% and 45.8% reported in 2007 and between 2009 and 2011, respectively (Table 1).…”
Section: Results Prevalence Of Rsv Circulating In Iransupporting
confidence: 90%
“…Figure presents the number of influenza‐like illness specimens and the rate of influenza positive specimens from October 2011 to November 2012 in Yaounde, Cameroon. As reported in two previous studies in Cameroon, our study shows a clear seasonal trend of the circulation of influenza viruses in Cameroon with peaks occurring from October to November. There was a low rate of influenza circulation from January to July with high numbers of suspected specimens.…”
Section: Introductionsupporting
confidence: 88%
“…The incidence of co‐infections in paediatric positive results (21.7%) is marginally higher than described in other studies (11.3–20.6%), with previous studies also demonstrating lower co‐infection rates in adults (5.5%) . The high proportion of adenovirus infections presenting as a co‐infection has also been recently described amongst children with CAP .…”
Section: Discussionmentioning
confidence: 50%